Letter from J. G. Washington to James Curtis Booth, August 10, 1855 - Washington, J. G. (1855)
J. G. Washington, of the United States Treasury Department, writes to James Curtis Booth (1810-1888) to confirm Booth's bills have been received.
Keywords: Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States; Washington, J. G.